Abilities, Motivations, and Opportunities of Furloughed Employees in the Context of Covid-19: Preliminary Evidence From the UK - Szulc, Joanna Maria; Smith, Rachael (Frontiers in Psychology, 2021)
The Covid-19 global pandemic is a crisis like no other, forcing governments to implement prolonged national lockdowns in an effort to limit the spread of the disease. As organizations aim to adapt and remain operational, employers can suspend or reduce work activity for events related to Covid-19 and claim government support to subsidize employee wages. In this way, some employees are placed on furlough (i.e., temporary unemployment) as opposed to being made redundant. While the impact of such schemes on global economy attracted much attention, their micro-level impact on individual employees is still unknown. Building on the ability-motivation-opportunity (AMO) framework, this pilot study explores how employees’ perceptions of abilities, motivation and opportunities are affected as a result of furlough. Rapid ethnography including interviews, observations, and document analysis in a British organization provided insights into the perceptions and experiences of employees put on furlough and highlighted that all three elements of AMO are affected by the current situation, either positively or negatively. We identify theoretical contributions and suggest a number of AMO enhancing practices in the context of furlough.